In vitro efficacy of latex and purified papain from Carica papaya against Strongyloides venezuelensis eggs and larvae - Moraes, Dayane; Levenhagen, Marcelo Arantes; Costa-Cruz, Julia Maria; Costa Netto, Antônio Paulino da; Rodrigues, Rosângela Maria (Revista do Instituto de Medicina Tropical de São Paulo, 2017)
Latex from Carica papaya is rich in bioactive compounds, especially papain, which may help to control parasitic diseases. This study evaluated the efficacy of latex from C. papaya and purified papain against Strongyloides venezuelensis. The Egg Hatching Test (EHT) and the Larval Motility Test (LMT) using fresh and frozen latex (250mg/mL), lyophilized latex (34mg/mL), and purified papain (2.8 mg/mL) were performed. Albendazole (0.025 mg/mL) and ivermectin (316 ppm) were used as positive controls. EHT and LMT were carried out through the incubation of each solution with S. venezuelensis eggs or larvae (± 100 specimens), and results were analyzed after 48h (EHT) or 24, 48, and 72h (LMT). EHT showed that latex preparations at higher concentrations (1:10 to 1:100) resulted in partial or complete destruction of eggs and larvae inside the eggs. The result from the 1:1,000 dilution was similar to the positive control. LMT showed effectiveness in all the tested dilutions compared to negative controls. Purified papain showed a dose-dependent response in the EHT. Purified papain (2.8 mg/ mL) showed similar results to lyophilized latex at 1:1,000 in the EHT. Latex and purified papain from C. papaya were effective against S. venezuelensis eggs and larvae in vitro, suggesting their potential use as an alternative treatment for strongyloidiasis.